Persepsi Para Pemangku Kepentingan Atas Kemampuan Pemelajar Matakuliah Bahasa Inggris Pada Sebuah STIE di Jawa Barat - Donny Hendry Fahsani (Jurnal Ilmiah Manajemen Kesatuan, 2022)
This study aimed to examine the ability of English learners at a business school in West Java and whether there were differences in perceptions among stakeholders regarding the ability of learners. This research was part of the English curriculum design project at the institution. This research used mixed methods. The sampling was carried out in a non-random stratified manner. Subsequently, the questionnaires were distributed to various stakeholders. We managed to capture 90 students’ questionnaires, 8 questionnaires for senior lecturers in expertise courses, 5 questionnaires for English teachers, 4 questionnaires from the Institution, and 5 questionnaires from the industry or graduate users. The interviews were conducted with the Institution. Using the nonparametric chi-square test (two-way chi-square test), the observation value was 28.1937, while the expected value was 13.2767, which means Ho was rejected and Ha was accepted. In other words, students' perceptions of their English language skills were in contrast to those of other stakeholders (English teachers, the lecturers, the institution, and the industry). The perceptions of other stakeholders were supported by the results of the TOEFL test which showed the low ability of students. These students' perceptions affected their motivation in learning English because they were satisfied. It is recommended that teachers and institutions straighten the perceptions of these students without being a demotivating factor in learning English at STIE. It would be even better, if teachers and institutions could motivate students so as to eliminate the cognitive dissonance. Keywords: Curriculum design, stakeholders’ perceptions, students’ capabilities, english for specific purposes, english for academic purposes, business english